MENINGKATKAN KEMAMPUAN VOCATIONAL PENYANDANG MENTAL RETARDATION DI’KAMPUNG IDIOT’ DESA SIDOHARJO, KECAMATAN JAMBON, KABUPATEN PONOROGO MELALUI BUDIDAYA KROTO - Melik Budiarti; Candra Dewi; Dian Permata Kusuma Dayu (Universitas Muhammadiyah Ponorogo, 2017)
A lot of people's attention focused on the empowerment of people who have both physical and psychological limitations. Attention is nothing but to help him in adjustments to face his life both in terms of communication, social relationships and to meet the needs of his life. The adaptive ability of people with mental retardation that they are trying to empower is their ability in vocational skills. This vocational skill is his ability in getting a job as a stock of his life. Developing vocational skills is not easy to require special ways in learning. Developing vocational skills by using economic empowerment in the environment of people who have mental retardation. Economic empowerment is done to improve the economic independence of people with mental retardation in idiot village, Sidoharjo village, Jambon district, Ponorogo. The aims is to empower people who have mental retardation economically adjusted to its ability that is with cultivation Kroto. The method used is to conduct counseling and training directly to people with mental retardation accompanied by their counterparts about economic empowerment with Kroto cultivation. Application of Kroto cultivation with two partners in Sidowayah hamlet, Sidoarjo village as a pilot project.